1995
DOI: 10.1248/cpb.43.408
|View full text |Cite
|
Sign up to set email alerts
|

Purines. LXX. An Extension of the "Phenacylamine Route" to the Syntheses of the 7-N-Oxides of 6-Mercaptopurine and 6-Methylthiopurine, and Antileukemic Activity of Some Purine N-Oxides.

Abstract: A full account is given of the first syntheses of 6-mercaptopurine 7-N-oxide (4) and 6-methylthiopurine 7-N-oxide (5). The synthesis of 4 followed a "phenacylamine route", which started from condensation of 4,6-dichloro-5-nitropyrimidine (15) with N-(4-methoxybenzyl)phenacylamine to form the phenacylaminopyrimidine derivative (11) and proceeded through conversion into the mercapto derivative, intramolecular cyclization between the NO2 nitrogen atom and the phenacyl carbanion to give 6-mercapto-9-(4-methoxybenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In contrast to this, ammonia in hot ethanolic solution under pressure added to the C ‐8 position, giving 288 (Scheme 49). [219,220] …”
Section: Ring Opening Of the Imidazole Moiety In Purinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this, ammonia in hot ethanolic solution under pressure added to the C ‐8 position, giving 288 (Scheme 49). [219,220] …”
Section: Ring Opening Of the Imidazole Moiety In Purinesmentioning
confidence: 99%
“…In contrast to this, ammonia in hot ethanolic solution under pressure added to the C-8 position, giving 288 (Scheme 49). [219,220] Heteroamines A-H are found in plant Heterostemma browni used in folk medicine for the treatment of tumors. Heteroamines A-C 289 a-c can be readily obtained from guanine [221] or 2-amino-6-chloropurine [222] and, due to the activated imidazolium ring, can be converted to heteroamines F-H 290 a-c via ring opening with dilute aqueous ammonia (Scheme 50).…”
Section: N-nucleophile Induced Ring Opening Reactionsmentioning
confidence: 99%
“…N -oxides 210 and 211 on the other hand have been shown to be weakly cytotoxic and have not be shown to possess any antimicrobial activity. [171] Studies by Parra and coworkers [172] showed that hypoxanthine 3- N -oxide 213 is the main chemical that elicits alarm reactions in zebrafish. These results are based on the observation of an efficaciously induced fear reactions and increase in the number of erratic movement episodes and jumps upon administration of this compound to zebrafish.…”
Section: Case Studies Of Heterocyclic N-oxide Drugs and Emerging Bmentioning
confidence: 99%
“…The oxidative transformation of purines into their N-oxide derivatives which are potent oncogenic agents introduces the possibility that such derivatives play an important role in various biological and clinical processes. [1][2][3] The presence of the N-oxide group in purines has been found to induce antibiotic activity. 4 Several purine N-oxides have been reviewed in relation to their oncogenic 5 and antitumor properties.…”
Section: Introductionmentioning
confidence: 99%